1996
DOI: 10.1002/(sici)1096-9861(19960923)373:3<451::aid-cne9>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Cultured basal forebrain cholinergic neurons in contact with cortical cells display synapses, enhanced morphological features, and decreased dependence on nerve growth factor

Abstract: Prior studies examining the dependence of basal forebrain cholinergic neurons (BFCNs) on nerve growth factor (NGF) for survival have reached differing conclusions depending on the experimental paradigm employed, suggesting the importance of environmental and developmental variables. The present study examined the NGF dependence of BFCNs and modulatory effects of target (cortical) neurons under the controlled conditions of dissociated cell cultures. Initial experiments found BFCNs (identified by using choline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 79 publications
2
19
0
Order By: Relevance
“…2B). These features are similar to those described for BFCNs in situ (Amaral and Witter, 1995;Houser et al, 1983;Shingai et al, 1990;Wenk et al, 1980;Woolf, 1991), and similar E. S. Tsai et alto the features described for these cells in both dissociated cell cultures (Dreyfus, 1989;Ha et al, 1996;Shingai et al, 1990) and in slice cultures (Baratta et al, 1996a,b;Robertson, 1992, 1993;Ga «hwiler et al, 1987).…”
Section: Abbreviations Used In the ¢Guressupporting
confidence: 83%
See 4 more Smart Citations
“…2B). These features are similar to those described for BFCNs in situ (Amaral and Witter, 1995;Houser et al, 1983;Shingai et al, 1990;Wenk et al, 1980;Woolf, 1991), and similar E. S. Tsai et alto the features described for these cells in both dissociated cell cultures (Dreyfus, 1989;Ha et al, 1996;Shingai et al, 1990) and in slice cultures (Baratta et al, 1996a,b;Robertson, 1992, 1993;Ga «hwiler et al, 1987).…”
Section: Abbreviations Used In the ¢Guressupporting
confidence: 83%
“…However, it remains possible that the development of the cholinergic phenotype occurs preferentially in cells that have settled down in a supportive environment or have established appropriate adhesive contacts on the slice. Other studies have reported expression of the cholinergic phenotype in dissociated cultures (Dreyfus, 1989;Hartikka and Hefti, 1988;Li et al, 1995;Nonomura et al, 1996;Shingai et al, 1990), however, the presence of exogenously applied neurotrophic factors or the presence of normal target cells is important for expression of the cholinergic phenotype and for survival (Dreyfus, 1989;Ha et al, 1996;Hartikka and Hefti, 1988;Li et al, 1995;Morse et al, 1993;Nonomura et al, 1996;Shingai et al, 1990). Grown in isolation, without target contacts or supplemental neurotrophins, the BFCNs do not thrive.…”
Section: Mechanisms Leading To the Non-random Distributionmentioning
confidence: 99%
See 3 more Smart Citations